Dependence of substrate work function on the energy-level alignment at organic–organic heterojunction interface. (22nd February 2019) - Foggiatto, Alexandre L.; Suga, Hiroki; Takeichi, Yasuo; Ono, Kanta; Takahashi, Yoshio; Kutsukake, Kentaro; Ueba, Takahiro; Kera, Satoshi; Sakurai, Takeaki
Abstract: The dependence of substrate work function (WF) on organic–organic heterojunction (OOH) interface was investigated using ultraviolet and X-ray photoelectron spectroscopy. We studied the interface of boron subphthalocyanine chloride (SubPc)/ α -sexithiophene (6T) deposited on MoO3, SiO2, Cs2 CO3 . We observed that MoO3 and Cs2 CO3 induce a p-doping and n-doping, respectively, due to the WF position, that can generate charge transfer at the OOH interface. However, the same effect was not observed after annealing the organic layers. Using scanning transmission X-ray microscope combining with near-edge X-ray absorption fine structure, we could observe that SubPc film became well-ordered after annealing the thin film. Thus, we suggested that the control of charge transfer arises from the reduction of the molecules misorientation on the film that induces a reduction in the density of gap states.